Oktjabr' i graždanskaja vojna v SSSR. Sbornik statej k 70-letiju I.I. Minca. [Pri učast. E.N. Gorodeckogo, I.P. Lejberova, G.I. Zlokazova i dr. Pod red. I.M. majskogo, M.V. Nečkinoj, V.M. Chvostova i dr.] (Nauka, 1966)
AN SSSR. Institut istorii.